Randomised, double-blind, placebo-controlled study investigating the effects of inorganic nitrate on vascular function, platelet reactivity and restenosis in stable angina: protocol of the NITRATE-OCT study. Issue 12 (20th December 2016) - Rathod, Krishnaraj S; Jones, Daniel A; Van-Eijl, T J A; Tsang, Hilda; Warren, Helen; Hamshere, Stephen M; Kapil, Vikas; Jain, Ajay K; Deaner, Andrew; Poulter, Neil; Caulfield, Mark J; Mathur, Anthony; et al.
Abstract : Introduction: The mainstay treatment for reducing the symptoms of angina and long-term risk of heart attacks in patients with heart disease is stent implantation in the diseased coronary artery. While this procedure has revolutionised treatment, the incidence of secondary events remains a concern. These repeat events are thought to be due, in part, to continued enhanced platelet reactivity, endothelial dysfunction and ultimately restenosis of the stented artery. In this study, we will investigate whether a once a day inorganic nitrate administration might favourably modulate platelet reactivity and endothelial function leading to a decrease in restenosis. Methods and design: NITRATE-OCT is a double-blind, randomised, single-centre, placebo-controlled phase II trial that will enrol 246 patients with stable angina due to have elective percutaneous coronary intervention procedure with stent implantation. Patients will be randomised to receive 6 months of a once a day dose of either nitrate-rich beetroot juice or nitrate-deplete beetroot juice (placebo) starting up to 1 week before their procedure. The primary outcome is reduction of in-stent late loss assessed by quantitative coronary angiography and optical coherence tomography at 6 months. The study is powered to detect a 0.22±0.55 mm reduction in late loss in the treatment group compared with the placebo group. Secondary end points include change from baseline assessment of endothelial function measured using flow-mediated dilation at 6 months, target vessel revascularisation (TVR), restenosis rate (diameter>50%) and in-segment late loss at 6 months, markers of inflammation and platelet reactivity and major adverse cardiac events (ie, myocardial infarction, death, cerebrovascular accident, TVR) at 12 and 24 months. Ethics and dissemination: The study was approved by the Local Ethics Committee (15/LO/0555). Trial results will be published according to the CONSORT statement and will be presented at conferences and reported in peer-reviewed journals. Trial registration numbers: NCT02529189 and ISRCTN17373946, Pre-results.